Social and Environmental Factors Associated with Physical Activity among Elderly in Yogyakarta City - -, Indriani -; Musdalifah, Andi; Prabaningrum, Nindha (Preventif : Jurnal Kesehatan Masyarakat, 2025)
The global and national increase in the elderly population has brought about various economic, psychological, and health-related challenges, as evidenced by the rising prevalence of chronic diseases such as hypertension, diabetes mellitus, cardiovascular disease, and obesity—many of which are linked to insufficient physical activity. Physical inactivity among the elderly can be attributed to several factors, including limited social support and restricted access to safe and age-friendly environments. Given the limited research in this area, it is essential to examine the relationship between social and environmental factors and physical activity among older adults in Yogyakarta City. This study aims to explore in greater depth how social and environmental factors contribute to the level of physical activity among the elderly. A cross-sectional study was conducted among individuals aged over 60 years, with a total sample of 297 elderly participants selected using purposive sampling based on defined inclusion and exclusion criteria. The research took place in Yogyakarta City between August 2024 and February 2025. Data were collected using a structured questionnaire that included demographic characteristics and social factors. Statistical analysis was performed using chi-square tests with SPSS version 22.0. Result: It showed that 57.9% of the elderly participants were physically active. Bivariate analysis revealed a significant association between social and environmental factors and physical activity (p < 0.005). Conclusion: The high prevalence of physical inactivity among the elderly highlights the need for local government strategies to promote physical activity through community-based approaches. These should involve enhancing social support and creating supportive environments that encourage active lifestyles among older adults. These findings are highly relevant for the development of community-based geriatric health policies